'Can you move your fat ass off the baseline?' Exploring the sport experiences of adolescent girls with body image concerns. Issue 4 (4th July 2021) - Vani, Madison F.; Pila, Eva; deJonge, Melissa; Solomon-Krakus, Shauna; Sabiston, Catherine M.
ABSTRACT: Body-related self-conscious emotions such as shame, guilt, envy, and embarrassment are highly prevalent in sport contexts and are associated with poor sport experiences and lower participation among adolescent girls. However, little is known about how body self-consciousness impacts quality sport among adolescent girls. The current study aimed to explore the sport experiences of girls with high body self-consciousness. Eleven adolescent girls ( M age  = 14.5 years) with an average of six years of experience in sport were purposefully sampled and participated in semi-structured interviews. Using a thematic analysis, six themes were identified: (i) navigating the culture of 'body talk', (ii) managing appearance- and fitness-related social comparisons, (iii) tension between appearance and sport competence evaluations, (iv) evaluation and competition in the sport culture, (v) compensatory behaviours (i.e. exercise) and restrictive eating to manage body self-consciousness, and (vi) duality of the body within and outside of sport. Collectively, the findings highlight the need to improve social practices in sport among girls in an effort to enhance adolescent girls' sport experiences.